Search for Annual 14C Excursions in the Past. Issue 2 (15th September 2016) - Miyake, Fusa; Masuda, Kimiaki; Nakamura, Toshio; Kimura, Katsuhiko; Hakozaki, Masataka; Jull, A J Timothy; Lange, Todd E; Cruz, Richard; Panyushkina, Irina P; Baisan, Chris; Salzer, Matthew W
Abstract: Two radiocarbon excursions (AD 774–775 and AD 993–994) occurred due to an increase of incoming cosmic rays on a short timescale. The most plausible cause of these events is considered to be extreme solar proton events (SPE). It is possible that there are other annual 14 C excursions in the past that have yet to be confirmed. In order to detect more of these events, we measured the 14 C contents in bristlecone pine tree-ring samples during the periods when the rate of 14 C increase in the IntCal data is large. We analyzed four periods every other year (2479–2455 BC, 4055–4031 BC, 4465–4441 BC, and 4689–4681 BC), and found no anomalous 14 C excursions during these periods. This study confirms that it is important to do continuous measurements to find annual cosmic-ray events at other locations in the tree-ring record.